1976
DOI: 10.1073/pnas.73.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of ferrocytochrome c by mitochondrial cytochrome c oxidase.

Abstract: Attempts to rationalize the kinetics of cytochrome c oxidation catalyzed by solubilized mitochondrial cytochrome c oxidase (ferrocytochrome c-.oxygen oxidoreductase, EC 1.9.3.1) have been based on assumptions of productive complex formation (Michaelis-Menten approach). However, the range of substrate concentrations used has not, in general, been sufficient to establish a general rate equation. Data adequate to derive such a rate expression are presented, as well as a method for estimation of constants which ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…When data were analyzed in a Lineweaver-Burk plot, two phases could be distinguished, each characterized by a K M and a k cat value resulting in a high and a low affinity phase as observed earlier (5, 20). The parameters for the high affinity phase are presented in Table II The K M can be taken as an apparent dissociation constant under certain conditions, and the work of several groups during the last few years has shown that K M is equivalent to K D for oxidase (21,22). We suppose from our earlier investigations that this holds at least for the condition of I ϭ 56 mM (6).…”
Section: Resultsmentioning
confidence: 91%
“…When data were analyzed in a Lineweaver-Burk plot, two phases could be distinguished, each characterized by a K M and a k cat value resulting in a high and a low affinity phase as observed earlier (5, 20). The parameters for the high affinity phase are presented in Table II The K M can be taken as an apparent dissociation constant under certain conditions, and the work of several groups during the last few years has shown that K M is equivalent to K D for oxidase (21,22). We suppose from our earlier investigations that this holds at least for the condition of I ϭ 56 mM (6).…”
Section: Resultsmentioning
confidence: 91%
“…1 also shows that cytochrome c, equimolar to the oxidase, is very effective in protecting the enzyme from carbodiimide modification and inhibition particularly with CMC. It is noteworthy that under these conditions only the high affinity cytochrome c binding site is occupied [20,21]. Higher temperatures increase the rate of reaction without changing the inhibition patterns and the extent of cytochrome c protection (see below).…”
Section: Resultsmentioning
confidence: 99%
“…Similar patterns were found at higher temperatures except for a greater efficiency of cross-linking in the presence of CMC with respect to EDC (not shown). On the base of kinetic studies it has been suggested that more than one binding site for cytochrome c exist on isolated cytochrome c oxidase [20,21]. Only the so-called 'high affinity binding site' is involved in these experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Errede et al 10 have published a detailed study of CCO kinetics, with an analysis of the results in light of several proposed mechanisms. The deduced rate equation for the reaction is complex, and includes many parameters relating to various steps in the proposed mechanism.…”
mentioning
confidence: 99%